Genetic parameters of production and reproduction traits of buffaloes in the Brazilian Amazon - Cassiano, Lisângela Aparecida Pinheiro; Mariante, Arthur da Silva; McManus, Concepta; Marques, José Ribamar Felipe; da Costa, Norton Amador (Pesquisa Agropecuaria Brasileira, 2004)
The aim of this study was to estimate genetic parameters, including genetic and phenotypic correlations as well as heritabilities, for production and reproduction traits of buffaloes in the Brazilian Amazon. Heritability estimates varied from 0.04 to 0.05 for FCI (first calving interval), 0.0 to 0.26 for CI (calving interval) and 0.0 to 0.25 for SP (service period), reflecting high environmental variation for these traits. For AFC (age at first calving) the heritabilities varied from 0.12 to 0.38. The Murrah breed showed the highest heritabilitiy for BW (birth weight) (0.62). Genetic correlations varied between 1.00 and -1.00 depending on the traits. There were negative genetic correlations between AFC and MFW (mature female weight) (-0.12 to -1.00 depending on breed) as well as between SP, BW and MFW (0.01 to -1.00). Permanent environment effects of the traits were low (0.000 to 0.155) and only that for CI in the Jafarabadi breed could be considered significant (0.458). Maternal effects for birth weight were low to medium (0.11, 0.17, 0.37 and 0.04 for Carabao, Jaffarabadi, Mediterranean and Murrah, respectively).